Hubungan antara Persepsi terhadap Kualitas dan Pemanfaatan Ruang Terbuka Hijau dengan Kesejahteraan Psikologis Anak - Afinnisa Rasyida (TATALOKA, 2021)
Gresik Regency has been trying to implement a green open space policy in the form of a child-friendly park. It is very substantial for Gresik Regency to have a park that can be both as outdoor space for children and also air pollution filter. This study aims to identify the relationship between perceptions of the quality and utilization of green open space with child psychological well-being. Data was collected using Perception of the Quality and Utilization of Green Open Space scale and Strength and Difficulties Questionnaire that obtained from parent’s assessment. The results suggested that there was a relationship between the perception of the quality and utilization of green open space with the child’s psychological well-being in the dimension of strength, specifically in developing prosocial behavior. However, there was no relationship in the dimension of difficulties. The results also obtained that the perception of the quality and utilization of green space in Gresik was good. Even so, the community still perceived the lack of park safety factors. They also infrequently visit the park. These results can be used as an evaluation for the Local Regional Government to improve the safety and comfort factor of the park.